El saber de la madre sobre estimulación temprana en el niño menor de un año - Marchena Ticlio, Estefany Rosa (2020)
The purpose of this research was to study "The knowledge of mothers in early stimulation in children under one year", with the objective of analyzing this knowledge and its implications. The theoretical approach was based on concepts of knowledge according to Japiassú and Abbagnano, early stimulation according to Peralta, mother according to Fernandez and child under one year according to WHO. The qualitative approach and the critical-reflexive method associated with Freire's pedagogy were chosen, the dynamics was the tree of knowledge, in a meeting, with six participants. The techniques used were: collective interview, group discussion and participant observation, based on dialogue, in order to encode topics, decode sub-themes and recode the synthesis, into four analytical categories: The first category, Mother-Child Interaction, was divided into four themes: 1) Prenatal Stimulation; 2) Distinction and recognition before external stimuli; 3) Fetal response to external stimuli; 4) Perception of the fetus. The second category, maternal skills, with four themes: 1) Safety and confidence of the mother with the child; 2) Early stimulation; 3) Thoroughness of the mother towards the child; 4) Creativity of the mother with the child. The third category, everyday knowledge, with three themes 1) Integral development; 2) Skills development; 3) Nutritional Stimulation. And the fourth category, maternal disposition of which two themes were generated: 1) Love and lullaby of the mother towards the child; 2) The game.